Meta-analysis of the effects of exercise interventions on dialysis patients with cardiac function disorders - Liu, Huizhen; Zhang, Ming; Chen, Minqi; Chen, Liusi; Huang, Tingrong; Ye, Zhao (Frontiers in Medicine, 2025)
BackgroundProlonged dialysis can lead patients to multiple complications, with heart failure being the most dangerous and the leading cause of death among dialysis patients. Concurrently, exercise has been shown to improve several indicators of heart function.MethodsA comprehensive search was conducted across seven databases. The search was limited to studies published between January 2010 and July 2024.Results(1) Compared to conventional care, exercise significantly increased the left ventricular ejection fraction (LVEF) in dialysis patients (MD = 2.00, 95% CI: 1.15–2.84, p < 0.001). Subgroup analysis revealed that combined aerobic and resistance exercise led to a more substantial increase in LVEF compared to aerobic exercise (MD = 2.78, 95% CI: 1.17–4.38, p < 0.001). Each workout lasting more than 30 min was associated with a significant increase in LVEF compared to sessions lasting 30 min or less (MD = 2.5, 95% CI:0.57–4.43, p = 0.001). An exercise intervention cycle of 10 to 12 weeks resulted in a significant increase in LVEF compared to cycles longer than 12 weeks (MD = 3.36, 95% CI: 2.04–4.68, p < 0.001). A weekly exercise frequency of more than three times per week significantly improved LVEF compared to three times per week or less (MD = 2.73, 95% CI: 1.21–4.25, p < 0.001). (2) In comparison to conventional care, exercise effectively reduced the left ventricular mass index (LVMI) of dialysis patients (MD = −7.93, 95% CI: −14.67–1.19, p = 0.02). However, exercise interventions did not demonstrate statistically significant improvements in pulse wave velocity (PWV), left ventricular end-systolic volume (LVESV), and left ventricular end-diastolic volume (LVEDV).ConclusionExercise can significantly enhance LVEF and decrease LVMI in dialysis patients. However, no significant improvements were observed in PWV, LVESV, or LVEDV. The subgroup analysis indicated that a combination of aerobic and resistance exercise had a better effect on improving LVEF compared to aerobic exercise, and exercise intervention with each workout lasting for more than 30 min, an exercise intervention cycle of 10 to 12 weeks, and an exercise frequency of more than three times per week were more effective in improving LVEF.